Penile rehabilitation with low‐intensity extracorporeal shock wave therapy in patients after prostate cancer surgery. Early physiological changes and postoperative follow‐up outcomes. Issue 12 (22nd September 2021) - Karakose, Ayhan; Yitgin, Yasin
Abstract: Introduction: To investigate the efficacy, safety and postoperative outcomes of using tadalafil and low‐intensity extracorporeal shock wave therapy (Li‐ESWT) on penile rehabilitation and preventing urinary incontinence after radical prostatectomy. Methods: In total, we included 66 patients who used only tadalafil (n = 32) in group 1 and used tadalafil and treated by Li‐ESWT (n = 34) in group 2. We noted International Index of Erectile Function (IIEF) 5, daily incontinence pad measurements at preoperative, postoperative 3rd, 6th and 12th months respectively. We also evaluated penis blood flow and neovascularisation by penile doppler ultrasonography at postoperative 3rd and 12th months for all patients. Statistical analyses were performed with SPSS version 18. A P ‐value < .05 was considered significant. Results: Preoperative demographic characteristics were similar in the two groups. There was a statistically significant improvement in IIEF‐5, which started at the 6th month and continued increasingly at the 12th month in group 2 compared with group 1. Also, there was a significant decrease in incontinence rate in group 2 compared with group 1 in the sixth month. Conclusions: Combined use of tadalafil and Li‐ESWT is highly effective and safe for the treatment of erectile dysfunction and for the prevention of urinary incontinence after prostate cancer surgery.